2008
DOI: 10.1080/09603120701694109
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the prevalence of respiratory diseases and allergies among schoolchildren in Chiang Mai, Thailand

Abstract: Air quality has seriously deteriorated as a consequence of population growth and urbanisation and respiratory diseases increased among residents of urban areas in Chiang Mai Province, Thailand. An International Study of Asthma and Allergies in Childhood (ISAAC) study was conducted among children attending schools located in the selected sites to assess the potential impacts of air pollution on health. The results showed that the prevalence of asthma was similar in all of the schools (approximately 5%; p = 1.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Two articles each were from Malaysia 28,29 and Thailand. 30,31 One article each was from Singapore 32 and Vietnam. 33 Four studies reported evidence that urban exposure was associated with asthma and allergic symptoms such as rhinitis and conjunctivitis.…”
Section: Urban Exposure and Chronic Respiratory Diseasementioning
confidence: 99%
“…Two articles each were from Malaysia 28,29 and Thailand. 30,31 One article each was from Singapore 32 and Vietnam. 33 Four studies reported evidence that urban exposure was associated with asthma and allergic symptoms such as rhinitis and conjunctivitis.…”
Section: Urban Exposure and Chronic Respiratory Diseasementioning
confidence: 99%
“…Although the causes of the worldwide "allergy epidemic" are not known, the growth in allergy prevalence is mainly centered in middle to low-income countries [ 2 ], which suggests that economic development may be driving the increase. In the Asia-Pacific region, this theory is borne out by data showing that allergy rates are higher in urban than in rural parts of Asian countries [ 8 9 10 11 ]. There is now emerging evidence of an interaction between irritants and allergens, whereby inhaled pollutants increase sensitization to allergens, and enhance airway hyperresponsiveness in susceptible people [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may occur because pollutants compromise the barrier function of airway epithelial cells, or because they enhance the immune response to airborne allergens [ 12 13 ]. The ability of pollutants to stimulate a nonallergic hypersensitivity reaction may explain the relationship between urbanization and rhinitis incidence in Asia and elsewhere [ 1 8 9 10 11 ]. Climate change may also impact on the development of allergic disease, and the combination of declining air quality and increasing global temperatures is likely to be driving the increase in allergy prevalence in developing and developed countries alike [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory effects, such as declined pulmonary function or chronic respiratory symptoms, were associated with air pollution (PM) in the Maemoh district, Lampang, and Bangkok [6264]. Early renal effects from chronic cadmium exposure, reduced cord serum T4 from organochlorine exposure, and allergy risk of allergic rhinitis and atopic dermatitis from air pollution (DEPs) were found in Tak and Chiang Mai, respectively [373967]. Increased cancer risk and DNA damage, and decreased DNA repair capacity, were detected in Bangkok and the Ron Phibul district, Nakorn Sri Thammarat.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is still an imbalance between industrialization and environmental protection. Rapid globalization and urbanization have led to the emergence of modern hazards, including pesticides [8101112131415161718192035707172]; heavy metals such as lead [2122232425262728303142434469], arsenic [3436], and cadmium [3739]; and air pollution such as traffic-related emissions in urban areas [47484950515263646567], VOC emissions from petrochemical industries [48546673], environmental tobacco smoke [575859], particulate matter from fires/burning [5667], and toxic gases from power plants [62].…”
Section: Discussionmentioning
confidence: 99%